Transmissibility prediction of coronavirus disease (covid-19) outbreak in early stages - Wong, Jordan; Kohbalan, Moorthy (2021)
The Covid-19 pandemic is still ongoing around the world. This study aims to predict the reproduction number, R0 for Covid-19 to measure the infectious level of this disease to the general population. To predict the reproduction number, a prediction method using the Probability Mass function is used with the dataset for the Covid-19 disease. This result has been divided into the first wave, second wave and third wave which suggest that the R0 is increased which correlate with the new strain of Covid-19 mutation “D614G” that is more infectious compared to the first wave strain. In a nutshell, with the R0 has been predicted, a containment plan is possible to curb the disease from spreading even further to the general population.